Endoscopic appendectomy for inverted appendix: A case report and review of literature - M M Zameer; Sanjay Rao; Gayathri Gopalakrishnan; Ashley D'cruz (Wolters Kluwer Medknow Publications, 2021)
Inverted appendix is a very rare anomaly and presents a diagnostic challenge. We report a case of inverted appendix in a 10-year-old boy and its management.